The Role of Supervisor and Student for Completing a Thesis - Sharma, Uma Nath (Tribhuvan University Journal, 2017)
Master’s degree students are required to write a thesis as a course alternative to a written examination of a paper. The purpose of this article is to understand and discuss the students’ perception on their own roles as a thesis candidate and the role of a supervisor in accomplishing a work of master’s thesis. For this, the candidates of master’s thesis were asked to respond a multiple choice item like questionnaire consisting of 12 sets of statements on the student-supervisor roles or responsibilities in three major aspects of thesis writing, namely topic/area of study, contact/involvement and the thesis/dissertation. The responses were analyzed descriptively using the software package – SPSS (Statistical Package for the Social Sciences). Analysis showed that the average students wanted to build a bridge (plan and manage the thesis writing) together with the supervisor so that they could cross it (accomplish the work of thesis writing). The students expected joint role of a supervisor. The supervisor and the student are recommended to share their expectations from each other, and build a mutual understanding of supervisor-student roles in advance and do accordingly for the successful completion of the thesis in reasonable time.